Performance Evaluation of Adaptive Algorithm with Linear Equalizer in MIMO OFDMA System - Sulong, Siti Maisurah; Idris, Azlina; Sarnin, Suzi Seroja (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Orthogonal frequency division multiple access (OFDMA) is one of digital modulation technique that allow many user to access during the same time and provide high speed data rate transmission in wireless communication system. Due to multipath propagation in real environment, wireless performance is degrading due to Inter Symbol Interference (ISI). In order to overcome this problem, Recursive Least Square (RLS) algorithm with Linear Equalizer will be used in this research. By adding space time frequency block code (STFBC) and multiple input multiple output (MIMO) antenna, this combination will prove their ability to reduce ISI and enhance system performance. The objective of this paper is also to evaluate Pairwise Error Probability (PEP) performance using combination of adaptive algorithm and LE. The PEP simulation results show the improvement of performance after reducing ISI and also prove that STFBC was able to achieve maximum diversity order in the MIMO OFDMA system.